Human iPSC‐derived neural precursor cells differentiate into multiple cell types to delay disease progression following transplantation into YAC128 Huntington's disease mouse model. (21st June 2021) - Park, Hyun Jung; Jeon, Juhyun; Choi, Jiwoo; Kim, Ji Yeon; Kim, Hyun Sook; Huh, Ji Young; Goldman, Steven A.; Song, Jihwan
Abstract: Objectives: To investigate whether human HLA‐homozygous induced pluripotent stem cell (iPSC)‐derived neural precursor cells (iPSC‐NPCs) can provide functional benefits in Huntington's disease (HD), we transplanted them into the YAC128 transgenic HD mouse model. Materials and Methods: CHAi001‐A, an HLA‐homozygous iPSC line (A*33:03‐B*44:03‐DRB1*13:02), was differentiated into neural precursor cells, and then, they were transplanted into 6 months‐old YAC128 mice. Various behavioural and histological analyses were performed for five months after transplantation. Results: Motor and cognitive functions were significantly improved in transplanted animals. Cells transplanted in the striatum showed multipotential differentiation. Five months after transplantation, the donor cells had differentiated into neurons, oligodendrocytes and astrocytes. Transplantation restored DARPP‐32 expression, synaptophysin density, myelin basic protein expression in the corpus callosum and astrocyte function. Conclusion: Altogether, these results strongly suggest that iPSC‐NPCs transplantation induces neuroprotection and functional recovery in a mouse model of HD and should be taken forward for clinical trials in HD patients. Abstract : Human HLA‐homozygous induced pluripotent stem cell (iPSC)‐derived neural precursor cells (iPSC‐NPCs) have multilineage differentiation potential and provide neuroprotection and functional recovery when transplanted into the YAC128 transgenic mouse model of Huntington's disease (HD).